2010
DOI: 10.3109/00365521.2010.513059
|View full text |Cite
|
Sign up to set email alerts
|

Association between bowel symptoms, symptom severity, and quality of life in Swedish patients with fecal incontinence

Abstract: Urgency and irritable bowel syndrome (IBS)-like symptoms were associated with decreased QoL in FI. Therefore, IBS should be considered as an important confounding factor in FI QoL studies. QoL in patients with FI was considerably decreased, in a similar extent as in patients with UC in relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In both our IBS cohorts, the presence of FI was associated with even greater impairment in quality of life. These findings are in agreement with a study on patients with FI where the presence of IBS was found to substantially impair quality of life, and also consistent with several other studies demonstrating that FI is associated with reduced quality of life . Regarding the association with psychological symptoms, there were differences between our cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…In both our IBS cohorts, the presence of FI was associated with even greater impairment in quality of life. These findings are in agreement with a study on patients with FI where the presence of IBS was found to substantially impair quality of life, and also consistent with several other studies demonstrating that FI is associated with reduced quality of life . Regarding the association with psychological symptoms, there were differences between our cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…In a population-based study of 2800 individuals performed in Olmsted County, Minnesota, fecal urgency and age were associated with FI symptom severity. 10 In addition, Walter et al 11 found in a study of 65 women with FI that bowel complaints of loose stools and urgency were associated with increased number of fecal leakages. In our study, we not only found fecal urgency to be associated with increased FI severity, but we also identified that a history of episiotomy, symptoms of UI, and diabetes mellitus were associated with more severe symptoms of FI.…”
Section: Discussionmentioning
confidence: 97%
“…10,11 Further evaluation that accounts for FI severity is needed and may help stratify future treatment modalities. In addition, no studies have looked solely at patients presenting with FI, gleaning information about mechanisms of severity that may inform future preventative efforts.…”
mentioning
confidence: 99%
“…In addition to fecal leakage the patients have other gastrointestinal symptoms, too, specifically those associated with irritable bowel syndrome (IBS). Walter et al [1] analyzed abdominal symptoms in FI patients and patients with ulcerative colitis served as controls. They found that the number of leakage episodes was not significantly correlated to decreased QoL, but urgency, feeling of incomplete evacuation, abdominal pain, bloating, and leakage of normal stool consistency were associated with decreased QoL.…”
Section: This Month In the Scandinavian Journal Of Gastroenterologymentioning
confidence: 99%